Kontribusi Pemikiran Imam Al-Asy’ari dan Imam Al-Maturidi dalam Pembentukan Karakter Religius Peserta Didik (Penelitian di MTs Bahrul Ulum Awipari Kota Tasikmalaya) - Yanto Maulana Restu; Faizan Ihwan; Nazwa Khaerunisa; Vindi Vindriani; Astri Nur Asfiah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the role of the theological thoughts of Imam Al-Asy'ari and Imam Al-Maturidi in strengthening the religious character of students at the Bahrul Ulum Awipari Junior High School in Tasikmalaya City. The background arises from the increasing character crisis, declining religious awareness, and weakening spiritual values ​​​​amid the impact of globalization and digital culture. These two theological figures of Ahlussunnah wal Jama'ah offer a moderate approach that emphasizes the balance between reason and revelation, making it a suitable basis for forming a critical, tolerant religious character and adapting to changing times. This study employs a descriptive qualitative method, collecting data through observation, in-depth interviews, documentation, and a review of supporting literature. The results of the study indicate that the theological values ​​​​of Al-Asy'ari and Al-Maturidi have been internalized in the teaching and learning process, school culture, and the habit of practicing the values ​​​​of tasamuh, tawazun, and i'tidal. The implementation of these values ​​​​has a positive impact on students' religious attitudes and behavior, especially in improving moderate religious understanding and character. This research contributes to the development of an Islamic education curriculum that integrates classical theological values ​​with religious character education that is relevant to the present day. Keywords: Imam Al-Asy'ari, Imam Al-Maturidi, Religious Character, Islamic Education, Religious Moderation